2017
DOI: 10.1080/14686996.2017.1361305
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of metals: a brief review of the characteristic microstructures and properties of steels, Ti-6Al-4V and high-entropy alloys

Abstract: We present a brief review of the microstructures and mechanical properties of selected metallic alloys processed by additive manufacturing (AM). Three different alloys, covering a large range of technology readiness levels, are selected to illustrate particular microstructural features developed by AM and clarify the engineering paradigm relating process–microstructure–property. With Ti-6Al-4V the emphasis is placed on the formation of metallurgical defects and microstructures induced by AM and their role on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
358
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 752 publications
(372 citation statements)
references
References 107 publications
(117 reference statements)
11
358
0
3
Order By: Relevance
“…Additive manufacturing (AM) of titanium alloys is gaining an increasing attention because many titanium alloys are expensive and hard to form/machine with conventional methods [3,4]. There are several methods for 3D printing metals including selective laser melting (SLM), selective electron beam melting (SEBM), directed energy deposition (DED) and binder jetting [5,6]. In the present study, we focus on selective laser melting (SLM) of Ti-6Al-4V that has attracted a lot of interest and results in a lamellar microstructure [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) of titanium alloys is gaining an increasing attention because many titanium alloys are expensive and hard to form/machine with conventional methods [3,4]. There are several methods for 3D printing metals including selective laser melting (SLM), selective electron beam melting (SEBM), directed energy deposition (DED) and binder jetting [5,6]. In the present study, we focus on selective laser melting (SLM) of Ti-6Al-4V that has attracted a lot of interest and results in a lamellar microstructure [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies regarding the LPBF modeling of Ti-6Al-4V (for recent reviews, refer to Refs. [1,8,9]). Karayagiz et al [10] reported the numerical and experimental analyses of temperature distribution during LPBF of Ti-6Al-4V.…”
Section: Introductionmentioning
confidence: 99%
“…At some superalloy compositions and 3D‐printing parameters, detrimental Laves phase particles are reported 15. More importantly, a high density of dislocations build up in the heat‐affected zone (HAZ), due to unavoidable (often local) deformation under high thermal stresses during printing 16,17. Upon solution treatment at elevated temperatures, these regions riddled with dislocations readily undergo recrystallization (RX)18 that renders the microstructure polycrystalline, which would significantly degrade the high‐temperature creep performance of blades (Figure S1 in the Supporting Information) 2.…”
mentioning
confidence: 99%